2016
DOI: 10.18203/2394-6040.ijcmph20160094
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of human brucellosis in Al-Qassim region, Saudi Arabia, between 2010 and 2014

Abstract: Background: Brucellosis, a zoonotic infection having an important public health issue in endemic countries; Saudi Arabia is one of these countries. The incidence of brucellosis in AlQassim region is much higher than the national one. Evaluation of the epidemiological situation of brucellosis is the first step in prevention and control. The objective was to describe the epidemiological characteristics of brucellosis in Al-Qassim region during the period between 2010 and 2014. Methods: All epidemiological survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
2
3
1
Order By: Relevance
“…Similar observations have been reported in previous Saudi studies [5,8]. Data on signs and symptoms of 1108 human brucellosis in the AL-Qassim region between 2010 and 2014, fever was the most common presenting symptom and accounting for 79.7% of the studied cases [25]. Arthralgia and joint pain and swelling were the second most common presenting symptoms in our study (48.1%) as in the previous one [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar observations have been reported in previous Saudi studies [5,8]. Data on signs and symptoms of 1108 human brucellosis in the AL-Qassim region between 2010 and 2014, fever was the most common presenting symptom and accounting for 79.7% of the studied cases [25]. Arthralgia and joint pain and swelling were the second most common presenting symptoms in our study (48.1%) as in the previous one [25].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the highest incidence was reported in summer (44.5%) and autumn (29.6%) seasons. A similar high peak of human brucellosis from May to October was also reported in similar Saudi studies [5,25,29], and a report from Jordan [30]. The incidence of brucellosis in humans corresponds to grazing season with an increase in the consumption of unpasteurized milk, camel milk, resulting in a rise in the number of cases in these seasons.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…There was no statistically significant difference between male and female gender in our study, likely because most infections were acquired via consumption of raw milk or cheese and not via direct contact with infected animals. Several other studies showed that men were more commonly infected than women likely because of their animal-related occupations [11,15]. The mean age of the patients in our study was 49 ± 20 year which is higher than the mean age reported in another study in Saudi Arabia [19].…”
Section: Discussioncontrasting
confidence: 77%
“…A study conducted in Al-Qassim region of Saudi Arabia describing the epidemiological characteristics of 4,283 cases of human brucellosis over five years showed that 51.1% of cases were Saudi citizens, and up to 46.5% were farmers and shepherds. The most common risk factor for the infection was direct contact with livestock animals followed by consumption of unpasteurized dairy products (80.7% and 55.6% respectively) [15].…”
Section: Introductionmentioning
confidence: 99%